The influence of pistia powder (Pistia stratiotes L.) in ration on the performance index and red blood cell profile of male Magelang duck - Fatmawati, Eka Rizky; Sarjana, Teysar Adi; Suprijatna, Edjeng; Santoso, Siswanto Imam; Setiadi, Agus (Faculty of Animal Science, Universitas Brawijaya, 2021)
The research aims at studying the influence of pistia powder (Pistia stratiotes L.) as feed material on the performance index and red blood cell profile of male Magelang duck. The materials used were 100 heads of 4-week old male Magelang duck. The treatments were: T0 (basal), pistia powder in T1, T2 and T3 of ration for male Magelang duck at 6%, 12% and 18%. The parameters observed were Performance Index (PI), number of erythrocytes, amount of hemoglobin, hematocrit level, MCV (Mean Corpuscular Volume), MCH (Mean Corpuscular Hemoglobin) and MCHC (Mean Corpuscular Hemoglobin Concentration). The research results showed that using pistia powder up to 18% significantly (P≤0.05) increased performance index (PI) and generally insignificantly (P>0.05) influenced the number of erythrocytes, amount of hemoglobin, hematocrit level, MCV and MCHC, but significantly decreased (P<0.05) MCH. The research concludes that pistia powder may be used up to 18% in ration to increase the performance index without influencing the red blood cell profile of male Magelang duck.